Pyrazinecarboxamides as potential elicitors of flavonolignan and flavonoid production in Silybum marianum and Ononis arvensis cultures in vitro - Tumova, Lenka; Tuma, Jiri; Dolezal, Martin (Molecules (Basel, Switzerland), 2011)
The effect of new synthetic pyrazinecarboxamide derivatives as potential elicitors of flavonolignan and flavonoid production in Silybum marianum and Ononis arvensis cultures in vitro was investigated. Both tested elicitors increased the production of flavonolignans in S. marianum callus and suspension cultures and flavonoids in O. arvensis callus and suspension cultures. Compound I, 5-(2-hydroxybenzoyl)-pyrazine-2-carboxamide, has shown to be an effective elicitor of flavonolignans and taxifoline production in Silybum marianum culture in vitro. The maximum content of silydianin (0.11%) in S. marianum suspension culture was induced by 24 h elicitor application in concentration of 1.159 × 10⁻³ mol/L. The maximum content of silymarin complex (0.08%) in callus culture of S. marianum was induced by 168 h elicitor application of a concentration 1.159 × 10⁻⁴ mol/L, which represents contents of silydianin (0.03%), silychristin (0.01%) and isosilybin A (0.04%) compared with control. All three tested concentrations of compound II, N-(2-bromo-3-methylphenyl)-5-tert-butylpyrazin-2-carboxamide increased the flavonoid production in callus culture of O. arvensis in a statistically significant way. The best elicitation effect of all elicitor concentrations had the weakest c₃ concentration (8.36 × 10⁻⁶ mol/L) after 168 h time of duration. The maximum content of flavonoids (about 5,900%) in suspension culture of O. arvensis was induced by 48 h application of c₃ concentration (8.36 × 10⁻⁶ mol/L).
Keywords: Amides; rostlinné extrakty; pyraziny; molekulární struktura; Molecular Structure; ostropestřec mariánský; Fabaceae; kultivované buňky; Plant Extracts; amidy; lidé; flavonoidy; Humans; Cells, Cultured; Flavonoids; Pyrazines; Flavonolignans; Silybum marianum; flavonolignany